The role of FDI inflows and export on economic growth in Sri Lanka: An ARDL approach - Md Reza Sultanuzzaman; Hongzhong Fan; Mahamud Akash; Banban Wang; Uddin Sarker Md Shaki (Cogent Economics & Finance, 2018)
This paper examines the long-run and short-run relationship between Foreign Direct Investment (FDI) inflows, exports, and economic growth in Sri Lanka over 1980-2016. The study implies Autoregressive Distributed Lag (ARDL) bounds testing approach to reveal the relationship between the variables. The study indicates that FDI inflows have a positive and significant relationship with economic growth in the long-run and short run. If FDI inflows increase, GDP growth will increase. But for exports, it has a negative and significant relationship with economic growth in the long-run. If exports increase, the GDP growth will decrease. Sri Lankan exports strongly depend on primary goods. There is a risk of finite resources and price volatility. It's not surprising for developing economy like Sri Lanka. Also, in the short run, exports have a positive and significant relationship with economic growth. If exports increase, GDP growth will increase significantly. The findings suggest that both FDI inflows and exports influence economic progress in Sri Lanka. Based on emerging market economies, FDI inflows are useful in improving the production process in the host country, and hereafter it will contribute to quality exports and the economic growth of Sri Lanka. Policymakers should emphasize to gear up all the barriers for the economic development of Sri Lanka.
Keywords: C10; F43; F15; 330; FDI Inflows; export; economic growth; ARDL